A rare case of composite type of gastric mixed adenoneuroendocrine carcinoma (Indian Journal of Case Reports, 2017)
Cancers exhibiting a combination of epithelial and neuroendocrine features can occur in various organs. In the WHO classification of neoplasms of the gastrointestinal tract, such tumors are called “mixed adenoneuroendocrine carcinomas”. They may be composite, combined or amphicrine type. We present here a rare case of composite adenocarcinoma and neuroendocrine carcinoma of stomach.